GENTLE HUMAN TOUCH ON CHANGES IN BLOOD PRESSURE OF PREMATURE BABIES IN THE PERINATOLOGY ROOM OF IBNU SINA HOSPITAL MAKASSAR - Harun, Rukmini; Purwati, Nyimas Heny; Sulaiman, Suhendar (Journal of Islamic Nursing, 2021)
Premature babies are babies born before 37 gestational age, many problems that often arise in premature babies such as hypoglycemia or immature hemodynamic status in this case is blood pressure. To maintain the stability of blood pressure, a nursing intervention is needed, namely Gentle Human Touch. This study aims to see how the influence of gentle human touch on blood pressure in premature infants by using quantitative research methods with a Quasi Experimental design to try out an intervention on a group of subjects with or without a comparison group, but not randomized to include subjects in the treatment or control group. with a sample of 9 people in the perinatology room of Ibnu Sina Hospital Makassar. The results showed that the p value: 0.001 which indicates that there is an influence of gentle human touch on the blood pressure of premature babies in the perinatology room of Ibnu Sina Hospital Makassar. It is hoped that the nurses on duty in the perinatology room will be able to implement this intervention.